Chemical and biological profiles of Tussilago farfara: Structures, nitric oxide inhibitory activities, and interactions with iNOS protein. (May 2017) - Xu, Jing; Sun, Xiaocong; Kang, Jing; Liu, Feng; Wang, Peixia; Ma, Jun; Zhou, Honggang; Jin, Da-Qing; Ohizumi, Yasushi; Lee, Dongho; Bartlam, Mark; Guo, Yuanqiang
Graphical abstract: Highlights: Four new and ten known compounds were isolated from Tussilago farfara . Their structures were elucidated by NMR spectroscopic data analyses. Compound 1 is a new sesquiterpene carrying a chlorine atom. All of the isolates showed NO inhibitory effects. Bioactive compounds showed strong binding with iNOS protein. Abstract: Tussilago farfara L. is a well-known herb plant and used widely in China, North Africa, and Europe. A phytochemical investigation to obtain new NO inhibitors resulted in the isolation of three new sesquiterpenes, one new phenolic derivative, and ten known compounds from the flower buds of T. farfara . Their structures were established on the basis of extensive analyses of nuclear magnetic resonance (NMR) spectroscopic data. All of the isolates exhibited inhibitory effects on LPS-induced NO production in BV-2 cells. The possible mechanism of NO inhibition was also investigated using molecular docking, which revealed the interactions of bioactive compounds with iNOS protein. The present study disclosed that flower buds of T. farfara have the potential to be developed into a functional food.